Respuesta :
Answer:
First, we can write:
x = 2 . ¯ 3
Next, we can multiply each side by 10 giving:
10 x = 23 . ¯ 3
Then we can subtract each side of the first equation from each side of the second equation giving:
10 x − x = 23 .¯ 3 − 2 . ¯ 3
We can now solve for x as follows:
10 x − 1 x = ( 23 + 0 . ¯ 3 ) − ( 2 + 0 . ¯ 3 ) ( 10 − 1 ) x = 23 + 0 . ¯ 3 − 2 − 0 . ¯ 3
9 x = ( 23 -2 ) + ( 0 . ¯ 3 − 0 . ¯ 3 )
9 x = 21 + 0
9 x = 21
9 x /9 = 21 /9
9 x /9 = 3 × 7 /3 × 3
x = 3 × 7 /3 × 3
x = 7 /3
Hope this helps!
Plz mark brainliest! ☜(゚ヮ゚☜)